Short-lived mixed affective states in bipolar disorder. (February 2020) - Aftab, Awais; Depp, Colin; Daly, Rebecca; Huege, Steven; Sutherland, Ashley; Soontornniyomkij, Benchawanna; Eyler, Lisa T.
Highlights: We characterized self-reported mixed mood states in people with bipolar disorder. Self-reported mixed states were overwhelmingly of short duration (≤ 24 h). They were more frequent in people with bipolar disorder compared to controls. They were associated with worse depression and functioning, and suicidal ideation.